DIVERSIFIKASI PRODUK KERAMIK HIAS TEKNIK CETAK TEKAN DAN ORNAMEN SGRAFFITO SENTRA SUMBERSEKAR DAU MALANG MELALUI PROGRAM KEMITRAAN MASYARAKAT - Ponimin, Ponimin; Irawanto, Rudi; Hariri, Afwan; bin Rani, Muhammad Faizal; Dewayani, Wahyu; Asmi Nusantari, Okta Viviana (Studi Budaya Nusantara, 2023)
The art of ceramic craftsmanship in the Sumbersekar Dau Malang center requires diversification act in product design. This is intended so that the products produced become innovative products and can be adjusted to the trends of the era and the tastes of consumers. To achieve this, press molding techniques and sgraffito ornaments in ceramic production were developed. The method applied in achieving the research purposes is the participatory creative method. The method contains the stages of the participatory creative process, including: a) the implementation team coordinates with program partners for activity implementation plans; b) preparation of tools and materials; c) implementation of participatory creative activities: making print models; reproduction process; making ornaments; smoothing; d) firing and finishing works; e) analysis of participatory creative processes and results in the development of decorative ceramic products. This creative and participatory work produces souvenir ornamental ceramic art products, which include: ornamental ceramic vase products, table accessories, and others. The process and results of this activity are expected to trigger the growth of creativity of local craftsmen, and further improve the creative economic aspects of the craftsmen.